Pemeriksaan Golongan Darah dan Rhesus Pada Siswa Kelas X SMA Negeri 11 Bengkulu Utara - Dian Fita Lestari; Fatimatuzzahra Fatimatuzzahra; Jarulis Jarulis (Jurnal SOLMA, 2020)
Abstract Blood type is hereditary and very important to know because it is associated with the success of blood transfusions, organ transplants, and hereditary diseases. In the blood type system that is often used is the ABO system, based on the presence of antigens A and B which are on the surface of red blood cells. And the rhesus blood group system is the second largest after the ABO system, which is determined based on the presence of antigen D. Because of the importance of knowing blood type and rhesus, it is necessary to have a blood type and rhesus examination of class X students in SMA Negeri 11 Bengkulu Utara. The method used in this dedication activity includes the preparation of materials used for the examination of blood groups and the execution of activities so that the results of each student's blood type are obtained. Blood type examination was attended by 34 students, 13 male and 21 female. Based on the results of the examination, the percentage of students who had blood type A was 29.4%, blood type B was 29.4%, blood type O was 29.4%, and AB blood type was at least 11.8%. The rhesus examination results, show that all students have positive rhesus (Rh +).